Comparison of the efficacy and safety of subthreshold micropulse laser with photodynamic therapy for the treatment of chronic central serous chorioretinopathy: A meta-analysis. Issue 17 (30th April 2021) - Wu, Zhizhong; Wang, Huixing; An, Junsheng
Abstract: Background: This meta-analysis was conducted to compare the therapeutic effect and safety of subthreshold micropulse laser (SML) vs photodynamic therapy (PDT) in treatment of chronic central serous chorioretinopathy (cCSC). Methods: PubMed, EMBASE, and the Cochrane Library were searched for all relevant studies published up to August 17, 2020. Data of interest were analyzed by STATA (version 14.0) software. Results: Four randomized clinical trials (RCTs) and 5 retrospective studies with 790 eyes were included in this meta-analysis after study selection. The results showed that SML significantly improved the best-corrected visual acuity (BCVA) compared with PDT at 6 to 8 weeks, 6 months, and 7 to 8 months in patients with cCSC (weighted mean difference (WMD) = −0.15, 95% confidence intervals (CI): −0.23 to −0.07, P  < .01; WMD = −2.83, 95% CI: −4.79 to −0.87, P  < .01; and WMD = −2.61, 95% CI: −4.23 to −1.24, P = .026, respectively). There was also a statistically significant difference between SML and PDT groups in the differences in the complete resolution of subretinal fluid (SRF) (risk radios = 0.388, 95% CI: 0.307 to 0.491, P  < .01). There were no significant differences between the SML and PDT in the overall effect with central macular thickness (CMT), adverse events, complete resolution of SRF and treatment response. Conclusions: Based on the available evidence, this meta-analysis demonstrated that SML may be considered as a competitive alternative to PDT for treating cCSC, and as the first-line treatment of cCSC.